Fie polinomul:
a) P(x)=X^3-X^2-X-1 si Q(x)=X+1
b) P(x)=X^3-X^2-X-1 si Q(x)=X-1
c) P(x)=X^4-3X^3-X^2+9 si Q(x)=X-3
Răspunsuri la întrebare
Răspuns de
29
a) P(x)=X-(X-1) => 2X+1 , Q(x)=X+1
b) P(x)=X-(X-1) => 2X+1 , Q(x)=X-1
c) P(x)=X^2-3X^3-9 => -3X-9 , Q(x)=X-3
b) P(x)=X-(X-1) => 2X+1 , Q(x)=X-1
c) P(x)=X^2-3X^3-9 => -3X-9 , Q(x)=X-3
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă